Restorative Justice Approach in Diversion System for Settlement of Criminal Cases for Children in Indonesia - Sarwadi Sarwadi; Bambang Tri Bawono (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2020)
This article aims to find out the general concept of restorative justice for children and to analyze the concept of restorative justice through the diversion system in Act No. 11 of 2012 concerning the Juvenile Criminal Justice System for the settlement of child criminal cases in Indonesia. In certain cases, children who are perpetrators of criminal acts are of particular concern to law enforcement officials. Therefore, various efforts to prevent and overcome children in conflict with the law need to be carried out immediately. Efforts to prevent and overcome children in conflict with the law today are through the implementation of a juvenile criminal justice system. To carry out guidance and provide protection for children, support is needed, both concerning institutions and more adequate legal instruments. One solution that can be taken in solving cases of juvenile crime is a diversion system. Diversion is not a peaceful effort but a form of punishment against children who are in conflict with the law in an informal way. Diversion is carried out to provide protection and rehabilitation to perpetrators in an effort to prevent children from becoming adult criminals. Diversion of child perpetrators of criminal acts is carried out by the three components of the criminal justice system in Indonesia, from the police, prosecutors to courts. Diversion is carried out to provide protection and rehabilitation to perpetrators in an effort to prevent children from becoming adult criminals. Diversion of child perpetrators of criminal acts is carried out by the three components of the criminal justice system in Indonesia, from the police, prosecutors to courts. Diversion is carried out to provide protection and rehabilitation to perpetrators in an effort to prevent children from becoming adult criminals. Diversion of child perpetrators of criminal acts is carried out by the three components of the criminal justice system in Indonesia, from the police, prosecutors to courts.